THE SELECTIVITY OF FISH TRAP ESCAPE GAP SIZE ON BOTANA FISH (Acanthurus reversus) - Tupamahu, Agustinus; Hehanussa, Kedswin; Haruna, Haruna (Bogor Agricultural University, 2024)
Fish trap is used due to its good prospect, particularly for demersal fish and reef fish in Maluku. A challenge of trap fisheries is the capture of various species of fish, along with a narrow size variation in the captured fish. To reduce the species diversity in the catch and allow the escape of young fish, an escape gap is recommended. This study aims to analyze the effect of different escape gap sizes on the fish that escape and their chances of being caught or escaping relative to the dominant catch. The study was conducted from July to September 2021 in the waters of Eri Village, Nusaniwe District, Ambon City, Indonesia. The experimental fishing method was used in the field. The results indicated that the size of the escape gap had no effect on the number of fish that escaped through each escape gap. The 50% probability of Achanturus reversus escaping from the size 2.0 cm escape gap is in the total length range of 21-22 cm, while from a 3.0 cm escape gap is 24-25 cm. Keywords: Fish pot, escape gap, selectivity